Clinical effectiveness observation of transperineal rectocele repair combined with puborectalis muscle release in the treatment of 26 patients with rectocele - Yang Yong; Huang Luqiao; Li Shanshan; Meng Qingliang; Xie Guangwei (结直肠肛门外科)
[Objectives] To analyze the clinical effectiveness of transperineal rectocele repair combined with puborectalis muscle release in the treatment of rectocele. [Methods] We retrospectively analyzed the clinical data of 26 female patients with rectocele who underwent transperineal rectocele repair combined with puborectalis muscle release at the Anorectal Department, Xuzhou Central Hospital from August 2022 to October 2023. The following indices were evaluated: operation time, intraoperative blood loss, surgical complications within 1 month postoperatively, symptom severity (assessed using the Longo’s obstructed defecation syndrome scoring system) before surgery, and at 3 and 6 months postoperatively, patient satisfaction (assessed using the Visual Analog Scale) at 3 and 6 months postoperatively, rectocele depth(measured by X-ray defecography) before surgery and at 6 months postoperatively, and recurrence during postoperative follow-up. Symptom severity and patient satisfaction were assessed via outpatient or telephone questionnaires. [Results] Of the 26 patients, the operation time ranged from 25 to 75 minutes, with a median of 36.5 (30.0, 47.5) minutes; intraoperative blood loss ranged from 0 to 50 mL, with a median of 2 (0, 4) mL. No complications such as rectovaginal fistula, rectal stenosis, or perineal infection occurred within 1 month postoperatively. Postoperative follow-up ranged from 8 to 22 months, with no recurrences. Twenty-one patients underwent X-ray defecography at 6 months postoperatively, while the remaining 5 patients declined due to personal reasons. All 26 patients completed the questionnaire assessments at 3 and 6 months postoperatively. Symptom severity scores gradually decreased from before surgery to 3 and 6 months postoperatively, and patient satisfaction scores were similar at 3 and 6 months postoperatively. Preoperatively, the median rectocele depth was 35.5 (32.8, 38.0) mm in all 26 patients, and 0 (0, 6) mm in the 21 patients who underwent X-ray defecography at 6 months postoperatively. [Conclusion] Transperineal rectocele repair combined with puborectalis muscle release exhibits good short-term clinical effectiveness in the treatment of rectocele and high patient satisfaction.